2006
DOI: 10.1143/jjap.45.9264
|View full text |Cite
|
Sign up to set email alerts
|

Superconductor-Based Quantum-Dot Light-Emitting Diodes: Role of Cooper Pairs in Generating Entangled Photon Pairs

Abstract: Realization of solid-state photon sources which are capable of on-demand generation of entangled single photon pair at a time is highly desired for quantum information processing and communication. A new method to generate entangled single photon pair at a time is proposed employing Cooper-pair-related radiative recombination in a quantum dot (QD).Cooper pairs are bosons and the control of their number states is not easy. The Pauli's exclusion principle on quasi-particles in a discrete state of a QD will regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 39 publications
1
42
0
Order By: Relevance
“…Since Cooper pairs collapse with energy relaxation, the Cooper-pair injection into the QD conduction band should be either resonant injection into a QD energy level with a type-I QD as shown in Fig. 1 or evanescent penetration with a type-II QD [20]. In this review paper, the theoretical treatment of the Cooper-pair radiative recombination is described and is compared with our experimental results.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Since Cooper pairs collapse with energy relaxation, the Cooper-pair injection into the QD conduction band should be either resonant injection into a QD energy level with a type-I QD as shown in Fig. 1 or evanescent penetration with a type-II QD [20]. In this review paper, the theoretical treatment of the Cooper-pair radiative recombination is described and is compared with our experimental results.…”
Section: Introductionmentioning
confidence: 95%
“…The remaining problem is that this is the second-order process and the EPP generation probability is low on the order of 10 −5 of the first-order single photon process [19]. We have proposed another scheme to generate EPPs employing superconductivity [20]. This is fundamentally a light emitting diode (LED) but the n-type electrode is replaced with a superconductor.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to develop the key device to connect the two research fields. We have proposed superconductor-based QD-light-emitting diode (SQLED) [1] as the key device to connect the two research fields. Recently Hayashi et al [2] reported the drastic enhancement of LED light output with superconducting effect with Nb electrode deposited n-type InGaAs/InGaAs/p-type InP quantum well (QW) structure.…”
Section: Introductionmentioning
confidence: 99%
“…7 We have proposed and have been working on a new method based on superconductors, where QEPPs can be generated through the radiative recombination of Cooper pairs. 8 Electrons in superconductors form Cooper pairs which are spin-singlet entangled pairs. 9 At a superconductor/normalmetal interface, Cooper pairs penetrate into the normal region by the proximity effect.…”
Section: Introductionmentioning
confidence: 99%